オゾン カンソク ノ ガイヨウ - 松原, 廣司; マツバラ, コウジ; Matsubara, Kouji (1997)
P(論文) 昭和基地におけるオゾン観測は, 1961年に開始された。南極変動研究(ACR)期間では従来から行われていたオゾン分光光度計およびオゾンゾンデによる観測に加えて, 地上オゾン濃度観測, 航空機によるオゾン濃度鉛直分布観測, 紫外域日射観測, 可視分光計による成層圏NO_2,O_3分光観測が実施され, また, 「しらせ」船上においては赤道域から昭和基地までのオゾンゾンデ・オゾン全量観測, が実施された。このうち, 地上オゾン濃度観測, 紫外域日射観測, 可視分光光度計による観測は現在も引き続き行われている。本稿では, 観測方法, 観測結果等の概要について観測開始以来の歴史的経過も含め報告する。 Ozone observations by the Japanese Antarctic Research Expedition (JARE) have been carried out since 1961. In the period of the Antarctic Climate Research Project (ACR) new observations were carried out in addition to historical observations using instruments such as Dobson spectrophotometer and ozonesonde. The new observations were as follows : 1) At Syowa Station surface ozone, UV-B radiation, columnar NO_2 and O_3,total ozone and aerosol determined using a Dasibi ozone meter, Brewer spectrophotometer, visible spectrometer, and Polar Patrol Balloon (PPB), respectively, 2) Columnar and vertical ozone amount from the equatorial region to Antarctica on board the research vessel SHIRASE. departmental bulletin paper